1991
DOI: 10.1108/02652329110001062
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Image as a Competitive Strategy: An Exploratory Study in Commercial Banks

Abstract: Owing to increased competition resulting from a decade of deregulation of the financial services industry, banks find themselves faced with the task of differentiating their product as a method for attracting new customers. The importance of bank image is examined as a competitive strategy for increasing customer traffic flow. A survey of 60 business undergraduates and 46 MBA students measured attitudes relating to bank size, atmosphere, innovativeness, and attributes relating to good service. Some significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…The managers agreeing to the notion that ATM helps clients banking needs, cut down long queues in the banking halls, and allow banking officials more time to interact with customers, show that the ATMs can be used to enhance service delivery and banks corporate images towards improved sales and market share. This finding is consistent with Leonard & Spencer's (1991) observation that a great majority of consumers perceived banks with ATMs as being either very successful or somewhat successful. It also relates to Essinger's (1999) argument that the role of technology in today's international financial community has changed significantly and is not only assisting with keeping record, but is also powering delivery systems, trading decisions, support systems and clearing and settlement systems.…”
Section: Managers Assessment Of Atms' Service Functionssupporting
confidence: 91%
“…The managers agreeing to the notion that ATM helps clients banking needs, cut down long queues in the banking halls, and allow banking officials more time to interact with customers, show that the ATMs can be used to enhance service delivery and banks corporate images towards improved sales and market share. This finding is consistent with Leonard & Spencer's (1991) observation that a great majority of consumers perceived banks with ATMs as being either very successful or somewhat successful. It also relates to Essinger's (1999) argument that the role of technology in today's international financial community has changed significantly and is not only assisting with keeping record, but is also powering delivery systems, trading decisions, support systems and clearing and settlement systems.…”
Section: Managers Assessment Of Atms' Service Functionssupporting
confidence: 91%
“…The banking industry has tried to take advantage of the productivity and customer service gains associated with technology by the provision of ATMs which consumers can use to carry out day-to-day banking transactions. Leonard and Spencer (1991) found that a great majority of customers perceived banks with ATMs as being either very or somewhat successful.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has also been reported [4][5] that in spite of the advantages of these new technologies, still a large number of customers fmd it difficult to use ATM, because they feel embarrassed and degraded due to lack of know how of using these technologies. Investigations revealed two opinions by the customers quotes; first non verbal communication, self independence, or no value judgment associated with ATMs and secondly; impersonality, fear of technology or vision problems [6].…”
Section: Introductionmentioning
confidence: 99%